Hobbes’ two accounts of law and the structure of reasons for political obedience - Venezia, Luciano Javier (2014)
Thomas Hobbes’s political theory contains conceptual theses on law, including an analysis of the way legal requirements affect practical reasoning. However, Hobbes’ account of law and the structure of reasons for political obedience is extremely ambiguous. In this paper, I show that Hobbes develops not one but two different accounts. Also, I argue that the two theories are in tension, something that Hobbes himself seems to recognize to some extent.